Problems of personnel administration in the government secondary schools in Bangkok, Thailand, as observed by their principals - Nimnualtong, Namtipya 1941- ([Quezon City s.n.], 1971)
The problems of personnel administration in 40 government secondary schools in Bangkok, Thailand, as observed by their respective principals was investigated. The normative survey method was used with the questionnare as principal instrument for gathering data.
Thesis (M. Ed.)--University of the Philippines.
Keywords: School personnel management; School management and organization -- Thailand